The Effect of Providing Steamed Tempe on Hot Flashes Symptoms in Menopausal Women in the Mulya Mekar Health Center Area, Purwakarta Regency, Indonesia - Rosanti, Aan (HM Publisher, 2023)
The isoflavones in tempe, such as genistein and daidzein, are compounds known as phytoestrogens. Phytoestrogens are plant compounds that have a structure similar to the human hormone estrogen. Since decreasing estrogen levels is one of the main characteristics in menopause, the isoflavones in tempe have attracted the attention of researchers. They hypothesized that these phytoestrogens might help reduce menopausal symptoms, including hot flashes, because they can bind to estrogen receptors in the body. This study aimed to determine the effect of giving steamed tempe on the symptoms of hot flashes in menopausal mothers in the Mulya Mekar Health Center Area, Purwakarta Regency, Indonesia. This study is experimental research with a pre-post-test approach without a control group and uses primary data, namely measuring the severity scale of hot flashes symptoms. A total of 30 research subjects took part in this study. This study shows that the intervention of providing processed tempe is effective in reducing the severity of hot flashes symptoms in postmenopausal mothers. There was a decrease in the severity of hot flashes symptoms and was stated to be statistically different, p<0.05. In conclusion, there is an effect of giving steamed tempe on the symptoms of hot flashes in menopausal mothers in the Mulya Mekar Health Center Area, Purwakarta Regency, Indonesia.